2022
DOI: 10.1155/2022/7793187
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Regression Analysis to Identify the Soil and Other Factors Affecting the Wheat Yield

Abstract: In farming and related fields, numerous connections exist that should be distinguished quantitatively. Several factors affect the various crop yields in different dimensions. These factors may have relation with farmer’s practices or with quality of soil. In this study, our main focus is to explore the effect of soil and other factors on the wheat yield. Regression modeling plays an important role in the identification of such factors that greatly affect the crops yield. For reliable and valid results, one has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…One of the promises of a digital twin in crop management is for the automatic prediction system to support in deciding the appropriate fertilization period [22][23][24]. Deploying the sensors which monitor the concentration of nutrients present in soil, humidity, and temperature in the real fields to make consistent quality checks.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the promises of a digital twin in crop management is for the automatic prediction system to support in deciding the appropriate fertilization period [22][23][24]. Deploying the sensors which monitor the concentration of nutrients present in soil, humidity, and temperature in the real fields to make consistent quality checks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One study employed an artificial neural network-based prediction algorithm to assess the influence of individual nutrients (N, P, K, Zn, and S) on various rice plant parameters. The algorithm indicated that optimal growth often occurs with nutrient doses below the maximum applied levels, while maximum yield is achieved at a 100% nutrient dose [22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The ZIP regression model combines two components: a zero component and a non-zero component [18,23]. The zero component captures the excess zeros in the data, while the non-zero component models the counts for non-zero outcomes.…”
Section: Zero-inflated Poisson (Zip) Regression Modelmentioning
confidence: 99%
“…One study employed an artificial neural network-based prediction algorithm to assess the influence of individual nutrients (N, P, K, Zn, and S) on various rice plant parameters. The algorithm indicated that optimal growth often occurs with nutrient doses below the maximum applied levels, while maximum yield is achieved at 100% nutrient dose [10].…”
Section: Literature Reviewmentioning
confidence: 99%